Genetic nature of hereditary diseases cattle and molecular genetic methods of diagnosis. (Experimental biology, 2015)
This article discusses the role of a point mutation in the etiology of hereditary diseases of cattle, the authors for thedetection of genetic defects BLAD, BC, CVM, DUMPS in tribal sires was used polymerase chain reaction and RFLPanalysis. Found that domestic breeding bulls are free from harmful genetic mutations.
Keywords: PCR; restriction amplificate; electrophoresis lethal autosomal recessive mutation; BLAD; Citrullinemia